Enhanced mechanical properties and large magnetocaloric effect in epoxy-bonded Mn0.98CoGe. (June 2018) - Zhu, F.; Lin, J.C.; Jiang, W.B.; Yang, C.; Li, L.F.; Zhang, X.K.; Song, W.H.; Zhu, X.B.; Tong, P.; Sun, Y.P.
Abstract: MnCoGe-based materials exhibiting large magnetocaloric effect (MCE) are potential candidates for magnetic refrigerants. However, the poor mechanical properties and intrinsic brittleness restrict their applications. Here, we report the synthesis of epoxy-bonded Mn0.98 CoGe composites and the evolutions of their microstructure, mechanical properties, and MCE with varying epoxy content. The mechanical properties and machinability are remarkably improved with epoxy resin addition. Meanwhile, the magnetic entropy change (ΔSM ) remains nearly unchanged when the content of epoxy is <5 wt%. Their relative cooling powder and the thermal conductivity are comparable to those of typical magnetic refrigerants with giant MCE. Graphical abstract: Unlabelled Image